Unemployment, Labour Market Programmes and Wage Determination: Evidence from the Czech and Slovak Republics - Henrik Huitfeldt (Uppsala University, Department of Economics, 2001)
This paper studies effects of unemployment and labour market programmes on real wages in the Czech and Slovak Republics using district paneldata for the period 1992-1998. Clear evidence of a wage curve exists in both countries. The estimated unemployment elasticity of pay is, however, higher in the Slovak Republic, than in the Czech Republic. The wage subsidy and the public works programme exert upward pressure on real wages in Slovakia. When accounting for effects from adjacent districts, a positive significant effect of labour market programmes is also estimated for the Czech Republic.
urn:nbn:se:uu:diva-2504
Keywords: J31; J68; P39; 330; Wage determination; Unemployment; Labour market programmes; Arbeitslosigkeit; Arbeitsmarktpolitik; Lohnniveau; Tschechische Republik; Slowakei